Peran generasi muda dalam melestarikan budaya bangsa melalui kerajinan batik - Aliyah, Muna Ma’rudatul; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
The younger generation has an important role in preserving the nation’s culture, especially in the midst of globalization that can threaten the sustainability of traditional cultural heritage. One form of national culture that has high historical and aesthetic value is batik craft. This article discusses the contribution of the younger generation in preserving and developing batik crafts as Indonesia’s cultural identity. The role of the younger generation is not only limited as consumers, but also as innovators, business people, and agents of cultural promotion. Preservation efforts are carried out through various means, such as learning batik techniques, introducing the philosophical values behind batik motifs, and utilizing digital technology to expand market reach. In addition, the younger generation can create innovations in batik design to keep it relevant to modern trends without losing its authenticity and traditional values. Their role is also seen in social media campaigns that effectively raise public awareness of the importance of batik as a UNESCO-recognized world cultural heritage. This article emphasizes that the involvement of the younger generation in the batik industry is not only a preservation effort, but also a strategy to strengthen the nation’s identity and support the local economy. With the active involvement of the younger generation, batik crafts have the potential to continue to grow, be accepted globally, and become the pride of Indonesia.